IMPROVING THE HEALTHCARE SYSTEM FROM THE PERSPECTIVE OF BIOETHICAL VALUES AND THE HISTORY OF MEDICINE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
By the 18th century, the widespread dissemination of Enlightenment ideas across several European countries, combined with the socio-political conditions of the era, led to the realization of a need to provide medical care to various segments of the population, particularly the military and specific groups of civilians. To this end, the idea of establishing specialized medical services and institutions subordinate to government administrative bodies was proposed. Consequently, state authorities began to assume certain responsibilities for organizing medical care and managing the healthcare system.